SCN‐SI‐021 achieving privacy and access control in pervasive computing environments. Issue 2 (8th February 2011) - Magkos, Emmanouil; Kotzanikolaou, Panayiotis
Abstract: This paper focuses on the inherent trade‐off between privacy and access control in pervasive computing environments (PCEs). On one hand, service providers require user authentication and authorization for the provision of a service, while at the same time end users require untraceability and unlinkability for their transactions. There are also cases where the anonymity of a specific credential must be revoked and a real identity be traced, in order to establish accountability. We analyze privacy and security requirements for PCEs and we show that existing privacy‐preserving access control schemes do not fully satisfy these requirements. Then we propose two approaches towards privacy‐preserving access control in PCEs. Our goal is twofold: (a) to enhance privacy by achieving untraceability and unlinkability even against malicious insiders and (b) to enhance security by achieving conditional traceability of user credentials, and if possible, non‐repudiation of evidence concerning the user's participating in a transaction. Finally, we analyze and compare the proposed schemes against existing schemes. Copyright © 2011 John Wiley & Sons, Ltd. Abstract : We analyze privacy and security requirements for PCEs and propose two approaches towards privacy‐preserving access control in PCEs. Our goal is twofold: (a) to enhance privacy by achieving untraceability and unlinkability even against malicious insiders and (b) to enhance security by achieving conditional traceability of user credentials, and if possible, non‐repudiation of evidence concerning the user's participating in a transaction. Finally, we analyze and compare the proposed schemes against existing schemes.